DEVELOPMENT OF A TEACHING PRESENCE-BASED ASYNCHRONOUS DISCUSSION FORUM TO ENHANCE STUDENT ENGAGEMENT IN THE INTRODUCTION TO EDUCATIONAL TECHNOLOGY COURSE - Anggara, I Wayan Agus Dimas; Sudatha, I Gde Wawan; Suartama, I Kadek (Jurnal Inovasi dan Teknologi Pendidikan, 2026)
Asynchronous learning in online environments requires instructional designs that can establish instructor presence and promote sustained student engagement. This study aimed to develop and examine the effectiveness of a teaching presence-based asynchronous discussion forum in enhancing student engagement in the Introduction to Educational Technology course. The study employed a research and development approach using the ADDIE model. Product validation involved three experts, product trials were conducted with 27 students, and the implementation phase involved 31 students from the Educational Technology Study Program at Universitas Pendidikan Ganesha. Product validity and practicality were analyzed descriptively, while the effectiveness of the forum on student engagement was analyzed inferentially using a paired sample t-test. The results indicate that the developed discussion forum achieved a very good level of validity and was practical to use. The effectiveness test showed a significant increase in student engagement following the implementation of the teaching presence-based asynchronous discussion forum. Therefore, the developed forum is effective in enhancing behavioral, affective, and cognitive engagement and is recommended as an asynchronous learning strategy in higher education.